2022
DOI: 10.3390/cells11182794
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Value of Serum Irisin in Prediction of Heart Failure with Different Phenotypes among Patients with Type 2 Diabetes Mellitus

Abstract: Recent studies have shown that circulating levels of irisin are prognostic factors in heart failure (HF), but no data are available on the predictive role of irisin in patients with type 2 diabetes mellitus (T2DM) and different phenotypes of HF. The aim of the study was to investigate whether serum levels of irisin predict HF in T2DM patients. We prospectively included 183 participants with T2DM aged 41 to 62 years (30 non-HF patients and 153 HF patients) and 25 healthy volunteers in the study and evaluated cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The discrepancy in the results principally regards its involvement in the inhibition of the adipogenesis process by downregulating PPARγ expression via the induction of Wnt/β-catenin signaling and the divergence between evidence observed in animal models and in humans [37,38,51]. Recent studies have indicated that irisin is a predictive marker of several pathologies, including sarcopenia, atherosclerosis, and heart failure [45,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in the results principally regards its involvement in the inhibition of the adipogenesis process by downregulating PPARγ expression via the induction of Wnt/β-catenin signaling and the divergence between evidence observed in animal models and in humans [37,38,51]. Recent studies have indicated that irisin is a predictive marker of several pathologies, including sarcopenia, atherosclerosis, and heart failure [45,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, acute HF, acute coronary syndrome, and acute myocardial infarction were associated with an increase in irisin levels, which is considered an adaptive factor that reduces endothelial damage by inhibiting inflammatory reactions and suppressing oxidative stress [185][186][187]. A low irisin level was described as an independent predictor of clinical outcomes in HF patients [188,189]. Although patients with HFpEF and AF had significantly lower irisin levels than those without AF [190], the role of irisin in predicting AF-related events, including relapse after electric cardioversion, has not yet been investigated.…”
Section: Irisinmentioning
confidence: 99%
“…Decreased irisin concentrations in T2DM patients are observed in parallel with cardiovascular complications [131][132][133]. They may have some predictive value in heart failure diagnosis [134,135] and be linked to nephropathy [136]. Some interventions, like sitagliptin treatment, increase serum irisin levels in T2DM patients [137].…”
Section: Irisinmentioning
confidence: 99%